Research progress on lactylation in atherosclerosis - MO Qin; LAN Yining; QIN Chao (Guangxi Yike Daxue xuebao)
Atherosclerosis (AS) serves as the primary pathological basis for cardiovascular and cerebrovascular diseases. Lactylation, a novel post-translational modification (PTM) linked to lactate molecules, functions as a critical interface between cellular metabolism and epigenetic regulation. This modification influences diverse pathways to regulate essential biological processes and has been closely associated with disease progression. Emerging evidence suggests that lactylation may participate in the pathogenesis of AS. This paper aims to summarize the biological characteristics of lactylation, and then specifically emphasizes the mechanisms by which lactylation participates in the development of AS through regulating endothelial cell function, macrophage polarization, and smooth muscle cell senescence.